2013
DOI: 10.1021/am400135c
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Protein Absorption and Cell Adhesion on Polymer-Brush-Grafted Poly(3,4-ethylenedioxythiophene) Films

Abstract: Tailoring the surface of biometallic implants with protein-resistant polymer brushes represents an efficient approach to improve the biocompability and mechanical compliance with soft human tissues. A general approach utilizing electropolymerization to form initiating group (-Br) containing poly(3,4-ethylenedioxythiophen)s (poly(EDOT)s) is described. After the conducting polymer is deposited, neutral poly((oligo(ethylene glycol) methacrylate), poly(OEGMA), and zwitterionic poly([2-(methacryloyloxy)ethyl]dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 51 publications
0
84
0
Order By: Relevance
“…Zhao et al synthesised PEDOT‐ g ‐P(OEGMA) brushes by ATRP grafting from electropolymerised films. The surfaces were shown to effectively prevent non‐specific adsorption of cells and proteins . The design of PEG‐functionalised CP‐based graft copolymers for biomedical applications was extended by Advincula et al with the use of a carbazole‐based macro‐CTA (Cbz‐CTA) to graft protein‐ and cell‐resistant poly(polyethylene glycol methyl ether methacrylate) (P(PEGMEMA)) brushes (Figure ) .…”
Section: Applications Of Functional Cp‐based Graft Copolymersmentioning
confidence: 99%
“…Zhao et al synthesised PEDOT‐ g ‐P(OEGMA) brushes by ATRP grafting from electropolymerised films. The surfaces were shown to effectively prevent non‐specific adsorption of cells and proteins . The design of PEG‐functionalised CP‐based graft copolymers for biomedical applications was extended by Advincula et al with the use of a carbazole‐based macro‐CTA (Cbz‐CTA) to graft protein‐ and cell‐resistant poly(polyethylene glycol methyl ether methacrylate) (P(PEGMEMA)) brushes (Figure ) .…”
Section: Applications Of Functional Cp‐based Graft Copolymersmentioning
confidence: 99%
“…17 Since then, grafted brushes have been used to improve CP hydrophilicity, 18 modulate electrochemical behavior of CP-based biosensors towards analytes of interest, 19 and recently to introduce antifouling behavior. 20 An additional layer of control over the surface properties can be added through the use of stimuli-responsive polymer brushes. Depending on the desired stimuli, surface properties can be modulated either via the electrochemistry of the CP backbone, or independently through changes in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 8(a), it can be observed that the cell attachment was much higher in the PEDOT:PSS/nHA/CS scaffold than the other scaffolds. The higher cell attachment in the PEDOT:PSS-containing scaffold might be due to the binding properties of the surface of the PEDOT:PSScontaining scaffold and its mechanical compliance, which increased the cell adhesion [33,34]. It was reported that the protein-binding properties of the surface can be modulated by the addition of PEDOT [33], which has a direct influence on cell adhesion.…”
Section: Cell Attachment and Cellmentioning
confidence: 99%
“…The higher cell attachment in the PEDOT:PSS-containing scaffold might be due to the binding properties of the surface of the PEDOT:PSScontaining scaffold and its mechanical compliance, which increased the cell adhesion [33,34]. It was reported that the protein-binding properties of the surface can be modulated by the addition of PEDOT [33], which has a direct influence on cell adhesion. It was also reported that applying electrical stimuli through conductive polymers can enhance tissue regeneration because of specific interactions between CPs and biological molecules, which serve as conducting biointerfaces [34].…”
Section: Cell Attachment and Cellmentioning
confidence: 99%